Comparison of intravoxel incoherent motion imaging, diffusion kurtosis imaging, and conventional DWI in predicting the chemotherapeutic response of colorectal liver metastases. Issue 130 (September 2020) - Zhang, Huan; Li, Wenhua; Fu, Caixia; Grimm, Robert; Chen, Zhiyu; Zhang, Wen; Qiu, Lixin; Wang, Chenchen; Zhang, Xiaowei; Yue, Lei; Hu, Xiaoxin; Guo, Weijian; et al.
Highlights: Functional changes occur before morphological size changes. We first compares these three functional MRI techniques in the response of CRLMs. Functional MRI are promising indicators for the early prediction of response. Abstract: Purpose: To assess the usefulness and performance of intravoxel incoherent motion imaging (IVIM) with diffusion kurtosis imaging (DKI) and conventional DWI for predicting the chemotherapeutic response of colorectal liver metastases (CRLMs). Method: A prospective study was conducted. Up to February 2018, forty consecutive patients treated with the standard first-line chemotherapy regimens were enrolled. MRI was performed within 1 week before chemotherapy, as well as 2–3 weeks and 6–8 weeks after chemotherapy. The apparent diffusion coefficient map, IVIM and DKI parameter maps were calculated using a prototype postprocessing software. The response was assessed by the Response Evaluation Criteria in Solid Tumors. The parameters were compared between the responding group (complete and partial response) and the nonresponding group (stable and progressive disease). Results: A total of 15 responding and 25 nonresponding patients were evaluated. Low baseline ADC, Dslow, and D values ( P  =  0.001, <0.001, and =0.003, respectively) and a high baseline K value ( P  =  0.002) were independently associated with a good response to chemotherapy. The combination of all the significant parameters yielded an AUC of 0.867. After treatment, the ADC, Dslow, and D values all showed an upward trend, while the K value showed a decreasing trend, but there were no significant differences ( P  >  0.05). Conclusion: The study showed that the pretreatment IVIM (Dslow ), DKI (D and K), and conventional DWI (ADC) parameters all demonstrated a good diagnostic performance in predicting the chemotherapeutic response of CRLMs.